The effectiveness of psychological skills training and behavioral interventions in sport using single-case designs: A meta regression analysis of the peer-reviewed studies. (November 2020) - Barker, Jamie B.; Slater, Matthew J.; Pugh, Geoff; Mellalieu, Stephen D.; McCarthy, Paul J.; Jones, Marc V.; Moran, Aidan
Abstract: We used a novel meta regression analysis approach to examine the effectiveness of psychological skills training and behavioral interventions in sport assessed using single-case experimental designs (SCEDs). One hundred and twenty-one papers met the inclusion criteria applied to eight database searches and key sport psychology journals. Seventy-one studies reported sufficient detail for effect sizes to be calculated for the effects of psychological skills training on psychological, behavioral, and performance variables. The unconditional mean effect size for weighted (Δ = 2.40) and unweighted (Δ = 2.83) models suggested large improvements in psychological, behavioral, and performance outcomes associated with implementing cognitive-behavioral psychological skills training and behavioral interventions with a SCED. However, meta-regression analysis revealed important heterogeneities and sources of bias within this literature. First, studies using a group-based approach reported lower effect sizes compared to studies using single-case approaches. Second, the single-case studies, (over 90 per cent the effect sizes), revealed upwardly biased effect sizes arising from: (i) positive publication bias such that studies using lower numbers of baseline observations reported larger effects, while studies using larger numbers of baseline observations reported smaller – but still substantial – effects; (ii) not adopting a multiple baseline design; and (iii) not establishing procedural reliability. We recommend that future researchers using SCED's should consider these methodological issues. Highlights: A positive publication bias exists in this literature. Few studies reported zero or negative effects. Smaller number of baseline observations yielded overly positive and disparate effects. PSTs and behavioral interventions assessed using SCEDS are effective in enhancing behavior change and performance. SCEDs are appropriate to detect meaningful changes in psychological, behavioral, and performance outcomes.